Effects of invasive larval bullfrogs (Rana catesbeiana) on disease transmission, growth and survival in the larvae of native amphibians - Andrew R. Blaustein; Devin K. Jones; Jenny Urbina; Ricky D. Cothran; Carmen Harjoe; Brian Mattes; Julia C. Buck; Randall Bendis; Trang Dang; Stephanie S. Gervasi; Rick Relyea (Biological Invasions, 2020)
The mechanisms by which invasive species negatively affect native species include competition, predation, and the introduction of novel pathogens. Moreover, if an invasive species is a competent disease reservoir, it may facilitate the long-term maintenance and spread of pathogens in ecological assemblages and drive the extinction of less tolerant or less resistant species. Disease-driven loss of biodiversity is exemplified by the amphibian–chytrid fungus system. The disease chytridiomycosis is caused by the aquatic chytrid fungus Batrachochytrium dendrobatidis (Bd) in anurans and is associated with worldwide amphibian population declines and extinctions. For amphibian species that metamorphose and leave infected aquatic habitats, the mechanisms by which Bd persists over winter in these habitats remains a critical open question. A leading hypothesis is that American bullfrogs ( Rana catesbeiana ), a worldwide invasive species, are tolerant to Bd and serve as a reservoir host for Bd during winter months and subsequently infect native species that return to breed in spring. Using outdoor mesocosms, we experimentally examined if two strains of Bd could overwinter in aquatic systems, in the presence or absence of bullfrog tadpoles, and if overwintered Bd could be transmitted to tadpoles of two spring-breeding species: Pacific treefrogs ( Pseudacris regilla ) and Cascades frogs ( Rana cascadae ). We found that only 4 of 448 total animals (one bullfrog and three spring breeders) tested positive for Bd after overwintering. Moreover, two of the three infected spring breeders emerged from tanks that contained overwintered Bd but in the absence of infected bullfrogs. This suggests that Bd can persist over winter without bullfrogs as a reservoir host. We found no effect of Bd strain on bullfrog survival after overwintering. For Pacific treefrogs, Bd exposure did not significantly affect mass at or time to metamorphosis while exposure to bullfrogs reduced survival. For Cascades frogs, we found an interactive effect of Bd strain and bullfrog presence on time to metamorphosis, but no main or interactive effects on their survival or mass at metamorphosis. In short, bullfrog tadpoles rarely retained and transmitted Bd infection in our experiment and we found limited evidence that Bd successfully overwinters in the absence of bullfrog tadpoles and infects spring-breeding amphibians.